2019
DOI: 10.29333/ajqr/6435
|View full text |Cite
|
Sign up to set email alerts
|

“Relational Transformation”: A Grounded Theory of the Processes Clinical Nurse-Educators (CNEs) Use to Assist Students Bridge the Theory-Practice Gap<br /> &nbsp;

Abstract: The theory-practice gap debate has permeated nursing literature for many decades. While some scholars insist on the existence of a gap and argue that the real value of nursing can only be represented by a broad theoretical framework that explains what nurses do; others have categorically rejected the need for nursing theories. The gap between theory and practice in nursing education has been highlighted as a pressing problem in developing countries where nursing education is in transition from hospital-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…And also Greenway et al (2019) opined that a solution to TPG may lie in transitional research whereby findings from significant research project are identified and applied at the patient or service user level. Osuji and El-Hussein (2016) suggested promotion of research within the practice context as a means of integration of knowledge into practice.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And also Greenway et al (2019) opined that a solution to TPG may lie in transitional research whereby findings from significant research project are identified and applied at the patient or service user level. Osuji and El-Hussein (2016) suggested promotion of research within the practice context as a means of integration of knowledge into practice.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Ajani andMoez (2011, 2021) made what may be called suggestive statement to the strategies for bridging the TPG in nursing under three sub-headings as thus: Reconstructing resources (Thomsen, 2019 andTiwaken et al, 2015); Recognizing training and Reconstituting roles (Mahmoud, 2014). From the perspective of Clinical Nurse Educators (CNEs), relational transformation as the outcome category in the study of Osuji et al (2019) communicates the clinical nurse educator's readiness and willingness to engage in a transformational and intentional relationship with nursing students to mentor, model and mold them into becoming professionals who can connect nursing theories to their practice. In bridging the gap between theory and practice in nursing practice and education, schools, educational policy and health policy makers, nursing services and other relevant government organs need to work in synergy.…”
mentioning
confidence: 99%